Personality rights: use of image from recorded classes (Research, Society and Development, 2022)
The scientific article exposes the general aspects of image rights from the perspective of remote classes. To better elucidate a problem, there was a discussion about the right of image and its concept, in order to demonstrate that it has two species. Then, a historical analysis of this institute and its legal and constitutional meaning was carried out. Soon minutia also already existed remote minutiae that already existed and are the training classes, important and the educators that are the training exercises, it was important and the educators are executed as training classes, it was important and the educators are executed. Subsequently, it was observed that the use of images of educators from remote classes without their consent in commercial studies is not legal and that a contract of assignment is required to stipulate this consent. Therefore, in the construction until this work, an exploratory methodology was used, with a construction of construction, to develop or studies of concepts, studies, experiences, real cases and decisions. Finally, the method used in the research was the indirect inductive method.